2009
DOI: 10.2320/matertrans.m2009157
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Strength and Corrosion Resistance of Copper Wires by Metallic Glass Coating

Abstract: Metallic glass was coated on copper (Cu) wires for enhancing their strength and corrosion resistance. The metallic glass coating has strong cohesion to the copper, and can effectively protect the wires from external forces and corrosive environments. Compared with bare Cu wires, the yield strength and the elastic strain limit of the coated wires have been significantly increased. The excellent corrosion resistance of the metallic glass coating has also provided essential shielding of the wires from chloride-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Fig. 1a shows schematic diagram of the vacuum system (8) in the continuous production unit. A crucible (3) for a molten metal with a heater (4) is equipped.…”
Section: Continuous Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 1a shows schematic diagram of the vacuum system (8) in the continuous production unit. A crucible (3) for a molten metal with a heater (4) is equipped.…”
Section: Continuous Processing Methodsmentioning
confidence: 99%
“…In industry, the development of coatings on wires is an issue of great importance for the durability and efficiency of practical applications in complex environments. Recently, Yu et al reported their result to produce BMG-coated copper bar composite with a diameter of 1 mm and investigated the compression property of the composite bar [8]. The continuous-BMG-coated wire, however, has seldom been studied because it is difficult to fabricate BMG-coated wire composite coil due to technological difficulties, such as how to obtain BMG coating, to control the interface between BMG coating and wire, and to obtain wire composite with no decreased mechanical properties.…”
Section: Introductionmentioning
confidence: 98%
“…Especially, novel selfassembled amorphous/crystalline composite with double layer or sandwich type structure has been developed originally on the principle of the liquid phase separation. Recently, Yu et al [20] and Chen et al [21] reported the results to synthesize BMG-coated copper bar and tungsten wire composites, respectively. In contrast to practical applications of the glass-coated composites, in this paper, the silvercoated NiNb-based metallic glass composite with the double layer or sandwich type structure may have potential applications in the fields of applied physics and electronics.…”
Section: Introductionmentioning
confidence: 98%
“…To break through the application restriction, exploiting attainable MGs as two-dimensional coatings is the most preferred way, since manufacturing coatings would not be limited by the thickness 9,10) . Moreover, the MGs of excellent corrosion resistance, high hardness, and good abradability are good candidate for wear/corrosion resistant coating on metallic components [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%